Fiber to the home : - Green, Paul Eliot (Wiley-Interscience, 2006)
Technicians, craftsmen, and engineers involved in installing fiber systems, Telecommunication network planners, Venture investors curious about the future of this dynamic industry sector, Research and product engineers who need to know the detailed architecture, cost, and performance imperatives of this "post-bubble" optical networking business opportunity, Students interested in a vibrant new industry with new jobs and new R & D challenges, Telecommunication regulators and attorneys who need a quick fix on what the technology is and what it does.